Rethinking Strategies To Improve Economic Development In Bandung Regency - Novi Eka Ratnasari; Sinta Ningrum; Elisa Susanti; Nova Magdalena Ginting (Economics Development Analysis Journal, 2022)
The success of a region's development is strongly influenced by the ability to develop the region's potential. This research aims to determine the potential and strategy of regional development, especially in Bandung Regency through an economic sector analysis approach. The method used in this research is descriptive research that uses an economic sector analysis approach through location quotient, Klassen typology, and shift-share analysis methods. Then combined with a document review of the RPJMN 2020-2024, RPJMD of the Bandung Regency Government 2016-2021, RTRW of the West Java Provincial Government 2009-2029, and RTRW of the Bandung Regency Government 2016-2036, which are supported by literature from journals, data, and other reports from the central and local governments relevant to the research. The results of this study are useful for the government, especially the Bandung Regency government, to further develop its leading sector, namely the processing industry sector, by planning the relocation and grouping of mature types and forms of industry per industrial area, and developing the geothermal energy sub-sector as a form of creation and utilization of environmentally friendly renewable energy. To improve the economics of both sectors, it is necessary to collaborate between them and with relatively underdeveloped sectors.